Platelet phagocytosis by leukocytes in a patient with cerebral hemorrhage and thrombocytopenia caused by gram-negative bacterial infection - Xiuji Wu; Youjun Li; Xiaoyang Yang (Journal of International Medical Research, 2022)
Bacteria-induced thrombocytopenia is a common clinical disease that is often ignored by clinical and scientific research. Thus, exploring the mechanism and principle of bacteria-induced thrombocytopenia could facilitate the development of new diagnostic, preventative, and treatment modalities for thrombocytopenia. This case report describes a case of platelet phagocytosis by neutrophils and monocytes in a patient with cerebral hemorrhage and thrombocytopenia caused by gram-negative bacterial infection. After the infection was eradicated, platelet phagocytosis was alleviated, and his platelet count normalized. Cellular immunity may be an important cause of bacteria-induced thrombocytopenia in patients with cerebral hemorrhage.